PENGEMBANGAN METODE TADABUR QURANI DALAM PEMBELAJARAN AGAMA ISLAM UNTUK MENINGKATKAN KEIMANAN: Studi pada Mahasiswa Universitas Pendidikan Indonesia Tahun 2009/2010. - Asyafah, Abas (2010)
, faith Faith improvement as the main goal of national / general / islamic education, uninteresting islamic learning in university level, limited effective Islamic teaching method which is developed from the source of religion of Islam (The Holy Quran), tadabur Quran which have not been applied into practice are problems of this research which raised the main question: How tadabur quran method in Islamic learning for increasing studens' faith?. This research and development was inititated by survey and literature research to draft tadabur qurani method in islamic learning for faith improvement. The draft is triangulated by Islamic learning and language expert and tested in limited tryout. After refinement, the method was empirically tested to students of Universitas Pendidikan Indonesia (UPI) who were attended Islamic learning subject in 2009/2010. Within the basis of theory of tadabur Quran, principles of islamic learning and islamic education, faith improvement as the core of the aim of education and the theory of general education/value, tadabur qurani method for faith improvement is finally made. The basis of this method is covering its definition, foundation, syntax, determining factors, steps and procedures of learning, and steps of internalizing value through tadabur qurani method. This method is systematically ordered, qualified to be used as theoritical dan practical reference, and effective to be used in Islamic learning for increasing students' faith because of its particular strengths. The effectiveness of the usage of this method will be powerful if it is supported by good Quran reading and arabic language ability. Theoritically, this method can reinforce principles of islamic learning and develop internalizing value which is ST4 (Sima'ah and tilawah, Tafhîm, Tadzawwuq, Tashdîq, andTajawwub. Practically, this method can be used in Islamic learning for university student. Further research is important to verify and develop this method within similar research. Recommendations of this research is addressed to (1) Department of general / value education to search for theoritical hints in Holy Quran and disseminate this method and facilitate it to be hold as intelectual property; (2) Lecturer of Islamic learning in University; to implement this method especially in Islamic faith improvement. (3) ADIPSI; to dissiminate this method in Islamic learning lecturer trainings, seminars, andscientific journal articles. Keywords: method, tadabur qurani, Islamic learningimprovement